Implementation Analysis on Parallel Parking Scheme for Autonomous Robots based on Nonholonomic Constraints - Annapandi, P.; Rajaram, S.P.; Prabhakar, G. (Current Signal Transduction Therapy, 2018)
Background: The whole thought is to demonstrate the parallel parking framework for self-ruling robots with the help of real-time embedded boards. Autonomous systems are outlined and developed by considering the non-holonomic requirements. PID controller is used to accomplish the servo reaction. The path planning scheme is created for parallel stopping of selfruling vehicles by gaining data from the sensor. Methods: The three vital stages engaged in safety parking are scanning, positioning and maneuvering. The scanning stage filters the stopping condition by ultrasonic separation estimating sensors. The positioning stage advances the vehicle and in reverse. It is mostly used to alter the appropriate separation from the begin point to turn point before moving. The parallel stopping of self-ruling robots with non-holonomic requirements are mimicked through MATLAB environment and prototype implementation is carried out through embedded platform. Results: Initially, open loop response of the non-holonomic vehicle is unstable and nonlinear in nature. Therefore the PID controller is used to control the response of the non-holonomic vehicle with minimum error based on the set point. The goal of this research is to attain the parallel parking scheme for non-holonomic vehicles, which is attained with the help of real time implementation. This implementation has been carried out using embedded processor with PID algorithm, sensors and actuators. Conclusion: Hence the paper depicts the structure of non-holonomic robotic vehicle and control with the help of PID controller. The parallel parking scheme has established using MATLAB programming and verified with the help of real time prototype. The paper proposed an idea of automated parking system in contrast to manual parking by the driver. The consumption of space, energy and time are minimized due to the automated parking scheme. Due to human error and negligence, harms such as collisions and accidents are occurred. These harms are reduced by implementing the parallel parking scheme in an intelligent manner. In future, Fuzzy based PD controller will be developed and implemented for the enhancement of parallel parking algorithm in robots.
Keywords: parallel parking